Monetary Policy after the Crisis - Marek Belka; Jens Thomsen; Kim Abildgren; Pietro Catte; Pietro Cova; Patrizio Pagano; Ignazio Visco; Petar Chobanov; Amine Lahiani; Nikolay Nenovsky; Cristina Badarau; Grégory Levieuge; et al. (SUERF - The European Money and Finance Forum, 2011)
On 4 March 2011, SUERF – The European Money and Finance Forum and the National Bank of Poland jointly organised a conference on the theme of: "Monetary Policy after the Crisis". Following a call for papers with a large number of submissions, the scientific committee selected 9 papers, which were grouped in three sessions addressing the following three research questions: First, what have we learnt from the crisis for the conduct of monetary policy? Second, what have we learnt from the crisis for the coordination of monetary, fiscal and macroprudential policies. And third, how did the Monetary Transmission Mechanism during the crisis function, and what can we expect for the future?
Keywords: E5; E52; F31; F42; F43; F47; G15; E43; F34; G10; P20; C61; E44; E58; E63; E51; G01; 330; Fixed exchange rate regimes; Denmark; monetary policy; foreign exchange policy; global imbalances; financial crisis; monetary policy; macroprudential regulations; structural regimes; money markets; sovereign CDS spreads; EU enlargement; monetary regimes; financial crisis; euro area; financial heterogeneity; monetary and budgetary policy rules; DSGE model; optimization; Monetary transmission mechanism; emerging economy; unconventional monetary policy; inflation expectations; long-term interest rates; Libor-OIS spread